Penilaian perlaksanaan KBSM : implikasi strategik terhadap pendidikan keguruan - Konting, Mohd Majid (1996)
This papers explores the assumption that educational innovations are changed at the implementation stage. Using an empirical evidence of the beliefs and practices of 41 nominated effective teachers of Form One who taught the subjects of Bahasa Melayu, the English Language and Mathematics, it shows that, contrary to the KBSM's philosophy, the teachers inclined to use traditional whole-class teaching strategies, to dominate classroom interaction and seldom practised cross-curricular integration. Its four implications for teacher education are discussed.